Development of a food safety toolkit for dry common beans (Phaseolus vulgaris l.) in Uganda using a Hazard Analysis and Critical Control Point (HACCP) approach - Aber, Harriet; Mulindwa, J.; Lung'aho, Mercy G.; Nyakundi, Fridah Nyabate; Jager, Matthias; Ugen, Michael Adrogu (African Journal of Food, Agriculture, Nutrition and Development, 2018)
Common beans (Phaseolus vulgaris L) may be contaminated with heavy metals and aflatoxins. Cooked beans may also be contaminated with micro-organisms due to poor hygiene and sanitation practices. Hazard Analysis and Critical Control Point (HACCP), which is a globally recognised food safety program, was proposed as a suitable program to minimise/eliminate the risk of contamination. Therefore, the objective of this study was to develop a HACCP plan for dry common beans in Uganda and an accompanying food safety toolkit. The seven principles of HACCP as outlined by Codex Alimentarius were followed to develop a HACCP plan for the dry common beans value chain in Uganda. A decision tree diagram was further used to identify each potential hazard at each processing stage and Critical Control Points (CCPs) along the chain. The identification of the CCPs was further supported by an evaluation of the actual risk and severity of the hazard. For the CCP identified, reliable control mechanism and corrective actions were established to fulfill the requirements set by the critical limits to guarantee the safety of the products. Verification and records systems were proposed to determine the effectiveness and traceability of the HACCP plan. For identified CCPs, a co-creation methodology was used to develop the food safety toolkit. This was carried out in four sessions that included a background of the chain actors’ ambitions to determine the suitability of the toolkit, assessment of CCPs, expert advice on the CCP and an exercise to develop concepts for each CCP. From the analysis, fourteen processing stages starting from land selection to cooking and serving were identified. Out of these, four stages were CCPs. These were land selection and preparation, storage, post-harvest drying, and cooking and serving. Hazards at the CCPs included heavy metals, mycotoxins, and micro-organisms such as S. aureus, E. coli, and Salmonella spp. A combination of good hygiene and sanitation practices and good agricultural practices were recommended as control measures against the hazards. To further equip the value chain actors with mitigation strategies, a food safety toolkit whose usefulness is to give the actors a systematic means to control identified CCPs was developed. In this regard, the toolkit and HACCP plan will complement each other. From the study results, implementation of the toolkit, followed by an assessment of its uptake and impact on livelihoods and food safety risks is recommended.